Integrative Chains of Demand and Supply in Multimodal Freight Transport - Grundey, Dainora (Ekonomika, 1999)
The article evaluates multimodal freight transport from the point of view of two economic factors, namely demand and supply. The objective of the paper is to present and evaluate criteria influencing supply and demand from theoretical and practical perspective. The origin and nature of commodities serve as recent catalysts in market economy. A suggestion is offered to evaluate freight transportation statistics by the value of commodities expressed in monetary units rather than tonne-kilometres as used before.